Mapping of Q-methodology studies in education in Turkey: A bibliometric analysis - YILMAZ VİRLAN, AYŞE (My University, 2023)
Extensive literature searches are commonly undertaken across various educational disciplines to thoroughly investigate, analyze, and elucidate the outcomes derived from research, trends, and underlying methodologies. The objective of provide a thorough and comprehensive examination of existing research papers conducted in the field of education in Turkey, specifically focusing on those that utilize Q-methodology in their research design. Additionally, this research attempts to analyze these research articles through bibliometric analysis. The present study examined research articles published in journals indexed by Scopus, Dergipark, Yöktez, and TR Index. A total of 194 articles were identified and included in the analysis. Following the application of the inclusion criteria, a bibliometric study was conducted to assess the publications in terms of their publication year, journal of publication, number of citations received, keywords utilized, and authorship. Based on the findings, it has been ascertained that only 20 research publications were undertaken in the domain of education within the context of Turkey. Furthermore, these investigations were found to be rather constrained in scope when juxtaposed with other fundamental scientific disciplines

Ergenlik, yaşam dönemleri arasında önemli bir evredir ve pek çok araştırmacının ilgisini çekmiştir. Bu nedenle, ergenlik kavramı ortaya çıktığı günden bugüne kadar literatürde ergenlik dönemi ile ilgili bilimsel araştırma ve yayın sayısında hızlı bir artış meydana gelmiştir. Ancak Türkiye’de ergenlik üzerine yapılan çalışmaların eğilimi hakkında bilgi eksikliği bulunmaktadır. Bu bağlamda, bu çalışmanın amacı Web of Science (WoS) veri tabanında taranan ve 1980 ile 2022 yılları arasında yayımlanan Türkiye adresli makalelerin bibliyometrik analiz yöntemi ile incelenmesidir. Verilerin analizi VOSviewer programı ile gerçekleştirilmiştir. 1980 yılından bu yana yayınlanan makale sayısı hızla artarak 10440’a ulaşmıştır. Yazarlar ve dergiler verimlilik açısından değerlendirildiğinde, tıp bilimlerindeki araştırmacıların ve dergilerin ön sıralarda yer aldığı görülmektedir. Hacettepe ve İstanbul Üniversiteleri yayın sayısı bakımından ilk sırada yer almaktadır. Ortak yazar ve ortak kelime analizi haritasında tıp, psikoloji, eğitim ve metodoloji ile ilgili kelimeler ve bu alanlarda çalışan araştırmacılar ön plana çıkmaktadır. Araştırmada elde edilen sonuçlar ışığında birtakım çıkarımlar yapılmıştır. Ayrıca araştırmacılara ve bazı kurumlara yönelik öneriler sunulmuştur.
Türkiye'de eğitimde Q-metodoloji çalışmalarının haritalanması: Bibliyometrik analiz
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Ergenlik; Bibliyometri; Bilimsel Haritalama; Türkiye Kaynaklı Yayınlar